2022
DOI: 10.1039/d1sc05663h
|View full text |Cite
|
Sign up to set email alerts
|

Linking metal–organic cages pairwise as a design approach for assembling multivariate crystalline materials

Abstract: A new strategy to design atomically precise multivariate metal–organic frameworks is presented. This is achieved by linking two preformed metal–organic cages via a precisely tuned Rh–aniline interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…64 The molecular nature of MOCs means that there are many ways to increase the complexity of their assemblies, with a simple scheme being to co-assemble at least two different MOCs into one material. Some initial studies have shown that this can be achieved by designing mutual coordination bonds between two different cages; 65 using ionic interactions based on charged MOCs to form MOC-based salts; 66 and mixture of charged MOCs with other molecular species such as polyoxometallates. 67 The possibility of forming molecular salts suggests this approach could be applied to other functional ionic components.…”
Section: Discussionmentioning
confidence: 99%
“…64 The molecular nature of MOCs means that there are many ways to increase the complexity of their assemblies, with a simple scheme being to co-assemble at least two different MOCs into one material. Some initial studies have shown that this can be achieved by designing mutual coordination bonds between two different cages; 65 using ionic interactions based on charged MOCs to form MOC-based salts; 66 and mixture of charged MOCs with other molecular species such as polyoxometallates. 67 The possibility of forming molecular salts suggests this approach could be applied to other functional ionic components.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In this feature article, we explain the influence of PSM on MOPs and their molecular chemistry, highlighting the interesting properties conferred to MOPs via PSM that are not found in other common porous materials. Whilst MOPs have attracted some interest as potential building blocks for the synthesis of extended materials, [27][28][29] that is beyond the scope of this article. In the first section of the present article, we cover the fundamental structural features of MOPs, aiming to facilitate visualisation of their surface chemistry for the subsequent sections.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering work on the co‐crystallization of varied MOPs reflects the potential of this approach toward fine tuning of the physicochemical properties of MOP‐based materials. [ 125,131 ]…”
Section: Perspectivesmentioning
confidence: 99%
“…Pioneering work on the co-crystallization of varied MOPs reflects the potential of this approach toward fine tuning of the physicochemical properties of MOP-based materials. [125,131] Another topic that we consider promising for the future is the molecular nature of MOP surfaces, which can enable stoichiometric control over the total number of appended functionalities, such that the final degree of cross-linking among the cages could be controlled. Indeed, although in this review we have focused on periodically extended materials, the molecular nature of MOPs offers vast potential to explore assembly of finite superstructures through stoichiometric, limited-growth steps.…”
Section: Perspectivesmentioning
confidence: 99%